IMPLEMENTASI PENEGAKAN DISIPLIN TERHADAP APARATUR SIPIL NEGARA YANG MELANGGAR KODE ETIK: Enforcement of Discipline for Civil Servants Who Violate the Code of Ethics - Ramadhani, Bella Mirtha; Wiratno (AMICUS CURIAE, 2024)
Civil servants are obligated to adhere to the prevailing legal regulations. However, there are still manyinstances where civil servants exhibit a lack of discipline and fail to comply with the applicable code ofethics. For instance, as illustrated in this case, there are instances where civil servants engage in sexualharassment towards students. The central issue revolves around the enforcement of disciplinarysanctions against civil servants who violate the code of ethics, as exemplified by Case Number4/Pid.Sus/2020/PN.MTR. This research also identifies the obstacles and challenges in implementingdisciplinary sanctions against civil servants who breach the code of ethics. The research methodology isnormative research of a descriptive, utilizing secondary data as the primary source of information. Thisdata is qualitatively analyzed, and conclusions are drawn through deductive reasoning. The findings ofthis study indicate that the actions taken by Lalu Mustajab, an ASN and the perpetrator in this case, haveviolated his obligations by sexual harassment behavior towards a students. Consequently, he could besubject to severe disciplinary penalties due to the abuse of authority.